Living With Assistive Robotics: Exploring the Everyday Use of Exoskeleton for Persons With Spinal Cord Injury - Lusardi, Roberto; Tomelleri, Stefano; Wherton, Joseph (Frontiers in Medical Technology, 2021)
Background: Recent advancements in sensor technology and artificial intelligence mechanisms have led to a rapid increase in research and development of robotic orthoses or “exoskeletons” to support people with mobility problems. The purpose of this case study was to provide insight into the lived reality of using the assistive robotic exoskeleton ReWalk. Method: We used ethnographic techniques to explore the everyday experience and use of the assistive robotic device. Results: We found that the appropriation and integration of the technology within the patient's everyday lives required a social and collaborative effort, which continued into use. The decisions to utilise the technology (or not) was closely tied to physical, social, cultural, environmental, and psychological factors. Consequently, there was much variation in patients' perception of the technology and opportunities for support. Four themes emerged: (a) Meaning of mobility—physical mobility represents more than functional ability. Its present socio-cultural meaning is associated with an individual's self-identity and life priorities. (b) Accomplishing body-technique—integration with the body requires a long process of skill acquisition and re-embodiment. (c) Adaptation and adjustment in use—successful use of the technology was characterised by ongoing adjustment and adaptation of the technology and ways of using it. (d) Human element—introduction and sustained use of the exoskeleton demand a social and collaborative effort across the user's professional and lay resources. Conclusions: This study highlights that the development and implementation of the technology need to be grounded in a deep understanding of the day-to-day lives and experiences of the people that use them.